ANALISIS BAURAN PEMASARAN (MARKETING MIX) DAN STRATEGI PENGEMBANGAN (STUDI KASUS PADA AGROINDUSTRI KOPI BUBUK CAP INTAN DI KOTA BANDAR LAMPUNG) - Dilla Sefa Ledy; Dwi Haryono; Suriaty Situmorang (Lampung University, 2019)
This study aims to analyze the marketing mix and development strategy which is applied to the agroindustry of Coffee Powder of Intan Brand in Bandar Lampung City. This research was conducted purposively in the agroindustry of Intan Brand Coffee Powder in determined Bandar Lampung City of Lampung Province. Data collection of this study was conducted from March to April 2017. This research is a case study, employed 14 people as respondents. The research data is analyzed by qualitative descriptive and SWOT analysis. The results of this study indicated that the marketing mix applied to the Intan Brand Coffee Powder agroindustry were (a) good quality product, (b) price determined by competitor price, (c) located at strategic place, and (d) promotion activities that have been applied by Intan Brand Agroindustry Coffee Powder was by face-to-face sales and sales promotion. The development strategy of Intan Brand Coffee Powder agroindustry in Bandar Lampung City were (a) the owner of agroindustry was determining the policy on utilizing the technology, (b) utilizing the location in the market and continuing to cooperate with PTPN 7 in order to have a bigger opportunities (c) maintaining good quality product so that the product could still competing with similar business at the market, (d) empowering the ability and human resource skills to resolve the limitations of capital in following technological developments.Key words: coffee powder, development strategy, marketing mix